# |
ODE |
Mathematica |
Maple |
\[
{}y^{4}+2 y+\left (x y^{3}+2 y^{4}-4 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{3}-2 x^{2} y+\left (2 x y^{2}-x^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y-3 y^{4}+\left (3 x^{3}+2 x y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+2 x^{2} y+\left (2 x^{3}-x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-a y = 1+x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = {\mathrm e}^{-x}
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right )^{2} y^{\prime }+y = \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime }-n y = {\mathrm e}^{x} \left (1+x \right )^{n +1}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+2 x y = 4 x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = y^{6} x^{2}
\] |
✓ |
✓ |
|
\[
{}1+y^{2} = \left (\arctan \left (y\right )-x \right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {2 y}{x} = 3 x^{2} y^{{1}/{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {x y}{-x^{2}+1} = x \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}3 x \left (-x^{2}+1\right ) y^{2} y^{\prime }+\left (2 x^{2}-1\right ) y^{3} = a \,x^{3}
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right )^{2} y^{\prime } = a^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}\sec \left (x \right )^{2} \tan \left (y\right )+\sec \left (y\right )^{2} \tan \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-x^{2} y\right ) y^{\prime }+y^{2}+x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {\left (1-2 x \right ) y}{x^{2}} = 1
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime }+\frac {2 y}{1+x} = \frac {x^{3}}{y^{2}}
\] |
✓ |
✓ |
|
\[
{}2 x -y+1+\left (2 y-x -1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{\sqrt {-x^{2}+1}} = \frac {x +\sqrt {-x^{2}+1}}{\left (-x^{2}+1\right )^{2}}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+\frac {y^{2}}{x} = y
\] |
✓ |
✓ |
|
\[
{}x \left (-a^{2}+x^{2}+y^{2}\right )+y \left (x^{2}-y^{2}-b^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {4 x y}{x^{2}+1} = \frac {1}{\left (x^{2}+1\right )^{3}}
\] |
✓ |
✓ |
|
\[
{}x^{2} y-\left (y^{3}+x^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x \left (-x^{2}+1\right ) y^{\prime }+\left (2 x^{2}-1\right ) y = a \,x^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2}+y^{2}+1-2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime } = m \left (x y^{\prime }-y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = y^{n} \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right ) y^{\prime }+1 = 2 \,{\mathrm e}^{y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x^{3} y^{3}-x y
\] |
✓ |
✓ |
|
\[
{}y+\left (a \,x^{2} y^{n}-2 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+6 y^{2}-3 x^{2} y\right ) y^{\prime } = 3 x y^{2}-x^{2}
\] |
✓ |
✓ |
|
\[
{}y \left (x^{2}+y^{2}+a^{2}\right ) y^{\prime }+x \left (-a^{2}+x^{2}+y^{2}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2} y^{3}+x y\right ) y^{\prime } = 1
\] |
✓ |
✓ |
|
\[
{}y y^{\prime } = a x
\] |
✓ |
✓ |
|
\[
{}\sqrt {a^{2}+x^{2}}\, y^{\prime }+y = \sqrt {a^{2}+x^{2}}-x
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right ) y^{\prime }+x -y = 0
\] |
✓ |
✓ |
|
\[
{}y y^{\prime }+b y^{2} = a \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 x y+\left (y^{2}-x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-x y^{\prime }+y = b \left (1+x^{2} y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}3 y+2 x +4-\left (4 x +6 y+5\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{3} y^{3}+x^{2} y^{2}+x y+1\right ) y+\left (x^{3} y^{3}-x^{2} y^{2}-x y+1\right ) x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{2}+y-\left (x^{3} y-3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+x^{2} y^{\prime } = x y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {n y}{x} = a \,x^{-n}
\] |
✓ |
✓ |
|
\[
{}\left (x -y\right )^{2} y^{\prime } = a^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+2 x {y^{\prime }}^{2}-y^{2} {y^{\prime }}^{2}-2 y^{2} y^{\prime } x = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-a \,x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3} \left (x +2 y\right )+3 \left (x +y\right ) {y^{\prime }}^{2}+\left (y+2 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3} = a \,x^{4}
\] |
✓ |
✓ |
|
\[
{}4 y^{2} {y^{\prime }}^{2}+2 y^{\prime } x y \left (1+3 x \right )+3 x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-7 y^{\prime }+12 = 0
\] |
✓ |
✓ |
|
\[
{}x -y y^{\prime } = a {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = -a y^{\prime }+\frac {c +a \arcsin \left (y^{\prime }\right )}{\sqrt {-{y^{\prime }}^{2}+1}}
\] |
✓ |
✓ |
|
\[
{}4 y = x^{2}+{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }+a x = 0
\] |
✓ |
✓ |
|
\[
{}y = 2 y^{\prime }+3 {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x \left (1+{y^{\prime }}^{2}\right ) = 1
\] |
✓ |
✓ |
|
\[
{}x^{2} = a^{2} \left (1+{y^{\prime }}^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{2} = a^{2} \left (1+{y^{\prime }}^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{2}+x y y^{\prime }-x^{2} {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y = y {y^{\prime }}^{2}+2 x y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y = \left (1+y^{\prime }\right ) x +{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (-x y^{\prime }+y\right ) = y {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\arcsin \left (y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{4 x} \left (y^{\prime }-1\right )+{\mathrm e}^{2 y} {y^{\prime }}^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x y \left (-x y^{\prime }+y\right ) = x +y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = x^{2}+y^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-2 x y y^{\prime }+2 y^{2}-x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y = y^{\prime } \left (x -b \right )+\frac {a}{y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}x y^{2} \left ({y^{\prime }}^{2}+2\right ) = 2 y^{\prime } y^{3}+x^{3}
\] |
✓ |
✓ |
|
\[
{}y = -x y^{\prime }+x^{4} {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}-9 y^{\prime }+18 = 0
\] |
✓ |
✓ |
|
\[
{}a y {y^{\prime }}^{2}+\left (2 x -b \right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x y^{\prime }-y\right )^{2} = a \left (1+{y^{\prime }}^{2}\right ) \left (x^{2}+y^{2}\right )^{{3}/{2}}
\] |
✓ |
✗ |
|
\[
{}\left (x y^{\prime }-y\right )^{2} = {y^{\prime }}^{2}-\frac {2 y y^{\prime }}{x}+1
\] |
✓ |
✓ |
|
\[
{}3 y^{2} {y^{\prime }}^{2}-2 x y y^{\prime }+4 y^{2}-x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+y^{2}\right ) \left (1+y^{\prime }\right )^{2}-2 \left (x +y\right ) \left (1+y^{\prime }\right ) \left (x +y y^{\prime }\right )+\left (x +y y^{\prime }\right )^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (y y^{\prime }+n x \right )^{2} = \left (y^{2}+n \,x^{2}\right ) \left (1+{y^{\prime }}^{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{2} \left (-{y^{\prime }}^{2}+1\right ) = b
\] |
✓ |
✓ |
|
\[
{}\left (x y^{\prime }-y\right ) \left (x +y y^{\prime }\right ) = h^{2} y^{\prime }
\] |
✓ |
✗ |
|
\[
{}{y^{\prime }}^{2}+2 y^{\prime } y \cot \left (x \right ) = y^{2}
\] |
✓ |
✓ |
|
\[
{}\left ({y^{\prime }}^{2}-\frac {1}{a^{2}-x^{2}}\right ) \left (y^{\prime }-\sqrt {\frac {y}{x}}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x +\frac {y^{\prime }}{\sqrt {1+{y^{\prime }}^{2}}} = a
\] |
✓ |
✓ |
|
\[
{}x y {y^{\prime }}^{2}+y^{\prime } \left (3 x^{2}-2 y^{2}\right )-6 x y = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}-4 x y y^{\prime }+8 y^{2} = 0
\] |
✗ |
✓ |
|
\[
{}{y^{\prime }}^{3}-\left (y^{2}+x y+x^{2}\right ) {y^{\prime }}^{2}+\left (x^{3} y+x^{2} y^{2}+x y^{3}\right ) y^{\prime }-x^{3} y^{3} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{3}+m {y^{\prime }}^{2} = a \left (y+m x \right )
\] |
✗ |
✓ |
|
\[
{}{\mathrm e}^{3 x} \left (y^{\prime }-1\right )+{y^{\prime }}^{3} {\mathrm e}^{2 y} = 0
\] |
✗ |
✓ |
|
\[
{}\left (1-y^{2}+\frac {y^{4}}{x^{2}}\right ) {y^{\prime }}^{2}-\frac {2 y y^{\prime }}{x}+\frac {y^{2}}{x^{2}} = 0
\] |
✗ |
✓ |
|
\[
{}y-\frac {1}{\sqrt {1+{y^{\prime }}^{2}}} = b
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+\frac {m}{y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y = 2 x y^{\prime }+y^{2} {y^{\prime }}^{3}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }+a \sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \sqrt {x} = \sqrt {y}
\] |
✓ |
✓ |
|
\[
{}x^{2} {y^{\prime }}^{2}-3 x y y^{\prime }+2 y^{2}+x^{3} = 0
\] |
✓ |
✓ |
|